Electro Cardiographic Features of Ptients With Tetralogy of Fallot - Al-Hamash, Sadiq M.; Al-Rubaiy, Fadhil; Hassan, Dhia’a (AL-Kindy College Medical Journal, 2007)
Background: For many decades, the ECG was the workhorse of non-invasive cardiac test and today although other techniques provide more details about the structural anomalies in congenital heart diseases, ECG is likely to be part of clinical evaluation of patients with such diseases because it is inexpensive, easy to perform and in certain situations may be both sensitive and specific. Objective: this study carried out to identify the pattern of ECG study in patients with TOF. Methods: this is a retrospective study of 200 patients with TOF, referred to Ibn Al-Bitar cardiac center from April 1993 to May 1999. The diagnosis of TOF established by echocrdiographic, catheterization and angiographic study. For each patient, the ECG tracing had been analyzed for rhythm, p-wave, P-R interval, QRS axis, duration and T-wave in V1 and any chamber enlargement. Results: The ECG analysis revealed that all patients had sinus rhythm, normal P-R interval and normal p-wave duration and amplitude, and normal QRS duration. All studied patients had one criteria of RVH and 95% of them had two or more of such criteria. Conclusion: we found that in the absence of RVH criteria, the diagnosis of TOF is unlikely and the present of northwest axis should indicate canal type VSD